Pengembangan Metode Integrasi Numerik dengan Frekuensi Batas yang Mampu Mereduksi Pengaruh Sinyal Pengganggu terhadap Hasil Integrasi - Zainal Abidin; Fandi Purnama; Budi Heryadi (Jurnal Teknik Mesin (Sinta 3), 2011)
In vibration measurements, integration process is often performed to acceleration as well as velocity signals. This integration process is usually done numerically in DSA (Dynamic Signal Analyzer) so that the result of integration has error with respect to the true (theoretical) value. Therefore, development of numerical integration methods with cutoff frequency are presented in this paper. This development produces equations which can reduce the influence of noise with respect to the result of numerical integration. Furthermore, these equations are validated with the simulation and experiment results. Base on the validation results, it can be concluded that the equations which have been derrived are correct.